Genetic Variability and Path Analysis Studies in Barley (Hordeum vulgare L.) - Matin, Mohammad Quamrul Islam; Amiruzzaman, Mohammad; Billah, Md. Motasim; Banu, Most. Bilkis; Naher, Nazmun; Choudhury, Dilwar Ahmed (International Journal of Applied Sciences and Biotechnology, 2019)
The present study was carried out to investigate the correlation coefficient, path analysis and genetic variability among some barley varieties for nine characters in a Randomize Block Design (RBD) with three replications in three environments of Bangladesh. High genotypic coefficient of variation (GCV) was obtained from grain/ spike (29.89 %), yield/ plant (28.72%) and effective tiller/plant (21.86 %) and spike length (13.56 %). The characters with high GCV indicated high potential for selection. The highest heritability (Hb) was observed for 1000 seed weight (95.09) followed by yield/ plant (93.98), grain/ spike (92.09) and spike length (69.93), days to heading (72.65) but the lowest Hb was identified for effective tiller/plant (22.41) followed by the plant height (34.21). Those traits with higher heritability may be considered for selection. Grain/ spike had the highest positive direct effect (5.65) on yield followed by 1000 seed weight (4.65), spike length (1.26), yield/ plant (0.66), days to heading (0.55) and days to maturity (0.34). These parameters were identified as direct selection. Direct negative effect on yield was shown by plant height (-0.32) and effective tiller/plant (-0.74). This was an indication of indirect selection. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 243-247